Mass, energy, entropy and exergy rate balance in a ranque-hilsh vortex tube - Edorta Carrascal; José María Sala Lizarraga (OmniaScience, 2013)
The purpose of this paper is to exhibit a laboratory practicum designed for the subject of Thermodynamics at the Department of Thermal Engineering of the University of the Basque Country. With reference to one of the problems stated in the text of Moran, Shapiro, Boettner, Bailey (2012), the balances of mass, energy, entropy and exergy are applied in a particular Control Volume, and the ideal gas model is used. Using a Ranque-Hilsh vortex tube (Ranque, 1934), the division of a compressed air flow into two streams at a lower pressure is achieved; one hot  whose temperature can exceed 100 °C and another cold that can reach temperatures below -40 °C. Therefore an air flow is divided into two, one hot and one cold stream, without any thermal interaction with hot or cold focuses. The vortex tube operation can serve to expose the bases of the first and second law of thermodynamics. Even, this practical lab can be used to give sense to one of the most known theoretical experiments in thermodynamics, such as the one of Maxwell's demon (Lewins & Bejan, 1999; Liew, Zeegers, Kuerten & Michalek, 2012). On the other hand once a compressed air source is provided, the material needed to prepare the lab is simple and affordable and it has a very interesting and suggestive appeal.